Epigenetics of aging and longevity - Moskalev, Alexey; Vaiserman, Alexander (aTranslational epigenetics series, 2018)
Epigenetics of Aging and Longevity provides an in-depth analysis of the epigenetic nature of aging and the role of epigenetic factors in mediating the link between early-life experiences and life-course health and aging. Chapters from leading international contributors explore the effect of adverse conditions in early-life that may result in disrupted epigenetic pathways, as well as the potential to correct these disrupted pathways via targeted therapeutic interventions. Intergenerational epigenetic inheritance, epigenetic drug discovery, and the role of epigenetic mechanisms in regulating specific age-associated illnesses—including cancer and cardiovascular, metabolic, and neurodegenerative diseases—are explored in detail. This book will help researchers in genomic medicine, epigenetics, and biogerontology better understand the epigenetic determinants of aging and longevity, and ultimately aid in developing therapeutics to extend the human life-span and treat age-related disease.--Provided by publisher.